Effect of bleaching on the cemento-enamel junction - Esberard, Roberta; Esberard, Renata R.; Esberard, Roberto M.; Consolaro, Alberto; Pameijer, Cornelis H. (Mosher & Linder, Inc, 2007)
Purpose: To evaluate the effect of various bleaching agents on the cemento-enamel junction (CEJ) of human teeth by scanning electron microscopy (SEM) analysis. Methods: 30 intact teeth were selected and longitudinally sectioned, yielding 60 specimens. Thirty specimens served as controls; the other 30 were divided into six groups with five specimens each (n= 5) and bleached according to six protocols (Group 1: External bleaching with 10% carbamide peroxide; Group 2: External bleaching with 35% hydrogen peroxide; Group 3: External bleaching with 35% hydrogen peroxide; Group 4: Internal/external bleaching with 35% hydrogen peroxide; Group 5: Internal/external bleaching with 35% hydrogen peroxide; and Group 6: Intracoronal bleaching with a paste of sodium perborate mixed with 9% hydrogen peroxide). After treatment the specimens were prepared and examined in a scanning electron microscope. Results: the bleaching agents used in this study caused morphological changes in the CEJ and increased dentin exposure.